Consumer preference for food attributes in Malaysia: case studies on broiler and beef - Abdul Hadi, Ahmad Hanis Izani (Taylor & Francis, 2013)
This study investigated the preferred food attributes, a critical component that determines consumer food choice, by Malaysian consumers. A case study was conducted on broiler and beef products. A conjoint analysis was performed to establish the trade-offs that consumers make between multiple sets of attributes in purchasing broiler and beef products. The findings indicated that the most preferred attribute for broiler was safety, followed by packaging, texture, and freshness. As for beef, freshness, packaging, and point of purchase were the preferred attributes. Consumers were also willing to pay higher prices for their preferred attributes.